Pengaruh Latihan Passing Bawah Menggunakan Sasaran Tembok Terhadap Ketepatan Passing Pada Permainan Bola Voli Di Min 2 Kota Bengkulu - Sahrul Wirayuda; Mariska Febrianti; Megi Personi (UNIVED Press, Universitas Dehasen Bengkulu, 2026)
This research was motivated by the low accuracy of underhand passing in volleyball games for extracurricular students at MIN 2 Bengkulu City, as evidenced by students' suboptimal ability to control the direction of the ball, coordinate movement, and mastery of basic underhand passing techniques. This study aimed to determine the effect of underhand passing training using a wall target on underhand passing accuracy in volleyball at MIN 2 Bengkulu City. This study used an experimental method with a one-group pretest-posttest design. The sample consisted of 12 extracurricular volleyball students selected using a total sampling technique. Data were collected through underhand passing accuracy tests before and after the underhand passing training using a wall target. The results showed an increase in underhand passing accuracy after the underhand passing training using a wall target. This was evidenced by an increase in the average pretest score from 24.08 to 28.58 in the posttest. Based on the results of the paired sample t-test, a significance value of 0.003 < 0.05 was obtained, indicating that there is a significant effect of underhand passing training using a wall target on the accuracy of students' underhand passing in volleyball games at MIN 2 Bengkulu City. Thus, training using a wall target can be used as an effective training method to improve students' underhand passing accuracy. Keywords: underhand passing training, wall target, underhand passing accuracy, volleyball.